Human-armadillo interaction in Ceará, Brazil: potential for transmission of Mycobacterium leprae - Kerr, Ligia Regina Franco Sansigolo (2015)
Several factors suggest that armadillos present an important risk for human leprosy infection. This study uses semi-structured interviews to better illustrate how human interaction with armadillos may increase the risk of leprosy transmission. The participants were all residents of the state of Ceará, in northeastern Brazil, all acknowledged contact with armadillos either through hunting, through cooking, or through consumption of its meat. This study raises important issues about contact between human beings and armadillos. The interviews provide evidence of numerous situations in which leprosy transmission via the armadillo is possible. At a minimum, people who hunt armadillos need to be made aware of the risk of infection.